The quick and the dead: Behavioral plasticity of anti‐predator responses in an Endangered mammal - Natasha D. Harrison; Chloe H. Frick; Adrian F. Wayne; Nicola J. Mitchell; Leonie E. Valentine; Julia C. Wayne; Derek Sandow; Rob Brewster; Ben L. Phillips (Conservation Science and Practice)
Abstract Populations isolated from predation inside predator‐free havens often exhibit a reduction in anti‐predator traits. The loss of such traits has a critical bearing on strategic conservation management, and so it is important to understand the basis of trait shift and how anti‐predator traits may be retained or restored. We explored plasticity in anti‐predator behaviors in an Endangered mammal, the woylie (Bettongia penicillata ogilbyi) at both the individual and population level. We quantified anti‐predator responses in individual woylies sourced from either a predator‐free haven (havened) or from an indigenous wild population (non‐havened) before and after translocation to a site with low densities of introduced predators, providing the first experimental test of anti‐predator responses and corresponding survival consequences in this species. Initially, the havened woylies had weak anti‐predator responses (lower agitation) compared with non‐havened animals. After exposure to predators, apparent survival was lower in the havened cohort compared to the non‐havened cohort. Those havened individuals that did survive, however, had stronger anti‐predator responses at the end of the study, approaching the level of response shown by their non‐havened counterparts. This within‐individual shift in behavior provides evidence for behavioral plasticity in this particular trait, suggesting that some aspects of anti‐predator behavior may be regained following exposure to predators and that this behavioral flexibility can be advantageous. At the same time, evidence of lower survival in previously havened individuals indicates that fixed differences in other traits remain and likely also contribute to survival. We discuss the implications of these findings for conservation management.